An ultra-light antibacterial bagasse–AgNP aerogel. Issue 6 (19th December 2016) - Shen, Zuguang; Han, Guocheng; Wang, Xiaoying; Luo, Jiwen; Sun, Runcang
Abstract : An antibacterial biomass-based ultra-light aerogel with AgNPs was fabricated, where AgNPs were synthesized with bagasse as a reducing and stabilizing agent. Abstract : This study reported the direct utilization of bagasse as an ultra-light aerogel with AgNPs for the first time. Firstly, AgNPs were synthesized in situ using a green route with bagasse, a by-product of the refined sugar industry. During the reaction, the crystalline region of cellulose in bagasse was destroyed, and some groups of bagasse were partly oxidized into CO of ketone, which confirms the reducing capacity of bagasse. Then, the obtained bagasse–AgNP composite was dissolved in EmimAc to prepare an aerogel with AgNPs. The aerogel piled up in slices, and its weight after swelling in water was about 19 times the dry weight, and the aerogel did not crush a flower branch because its density was only 0.035 g cm −3, although the mole and mass ratios of the Ag atom were 5.26% and 29.94% in the aerogel, respectively. Furthermore, the obtained aerogel showed a strong antibacterial effect, especially against E. coli and P. aeruginosa . This study not only provides an interesting way for bagasse to be applied directly, but also develops an antibacterial biomass-based ultra-light aerogel without AgNP dissociation.